2012
DOI: 10.1542/peds.2011-1556
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Difficulties in Children With Developmental Coordination Disorder

Abstract: Children with probable DCD had an increased risk of mental health difficulties that, in part, were mediated through associated developmental difficulties, low verbal IQ, poor self-esteem, and bullying. Prevention and treatment of mental health difficulties should be a key element of intervention for children with DCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
179
2
11

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(208 citation statements)
references
References 60 publications
11
179
2
11
Order By: Relevance
“…4 Children with developmental coordination disorder (with or without ADHD) have been found to be at increased risk of anxiety and depression. 19,20 In one study, children who had the disorder without ADHD reported depressive symptoms five times more often, and anxiety symptoms about one and a half times more often, than typical peers. 19 Other problems commonly associated with developmental coordination disorder are psychosocial difficulties, 21 overweight or obesity, 9,22 hypermobility of joints, 23 compromised physical A.…”
Section: How Is the Disorder Diagnosed?mentioning
confidence: 99%
“…4 Children with developmental coordination disorder (with or without ADHD) have been found to be at increased risk of anxiety and depression. 19,20 In one study, children who had the disorder without ADHD reported depressive symptoms five times more often, and anxiety symptoms about one and a half times more often, than typical peers. 19 Other problems commonly associated with developmental coordination disorder are psychosocial difficulties, 21 overweight or obesity, 9,22 hypermobility of joints, 23 compromised physical A.…”
Section: How Is the Disorder Diagnosed?mentioning
confidence: 99%
“…1 This plays a key role in their exploration of the world, academic performance, sporting abilities, involvement in social activities, and self-efficacy. 2,3 In recent literature, visuomotor performance of very preterm children has been commonly described with the widely used Beery-Buktenica Developmental Test of Visual-Motor Integration, 4 indicating widespread visuomotor integration deficits closely interrelated with poor motor performance.…”
Section: Discussionmentioning
confidence: 99%
“…1 This plays a key role in their exploration of the world, academic performance, sporting abilities, involvement in social activities, and self-efficacy. 2,3 In recent literature, visuomotor performance of very preterm children has been commonly described with the widely used Beery-Buktenica Developmental Test of Visual-Motor Integration, 4 indicating widespread visuomotor integration deficits closely interrelated with poor motor performance. 5 Although these outcomes clearly illustrate the negative impact of very preterm birth on visuomotor skills and related motor performance, there is a lack of understanding of the underlying mechanisms of visuomotor problems in very preterm children, which hampers opportunities for efficient treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, children with DCD have been reported to have a low self concept (Poulsen, Johnson, & Ziviani, 2011), high levels of anxiety (Pratt & Hill, 2011) and difficulty maintaining friendships ( Piek, Barrett, Allen, Jones, & Louise, 2005) compared to their age peers without motor difficulties. Some reports also indicate a higher incidence of more serious psychological and psychiatric disorders Green, Baird, & Sugden, 2006;Lingam et al, 2012) extending into adult life (Hill & Brown, 2013;Kirby, Williams, Thomas, & Hill, 2013). DCD has long been recognised and has been included in formal classification schemes since 1987 (APA, 1987).…”
Section: Introductionmentioning
confidence: 99%